Landslide characteristics triggering evacuations: A comparative study of community responses and disaster management approaches - Indratmoko, Satria; Koestoer, Raldi Hendro (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Landslides are one of the most dangerous geological disasters in the world due to the movement of earth material caused by gravity. Landslides also threaten the environment, property, and human life risks in high-risk areas. This study compares how landslide characteristics impact evacuation planning in Indonesia and various other countries. Methods: Utilizing a Systematic Literature Review (SLR) of studies published between 2019 and 2024, this research examines landslide characteristics that prompt community evacuation responses, such as landslide triggers, physical conditions, and the number of people affected. Findings: Findings reveal that while Indonesia and other high-risk countries face substantial landslide risks, challenges remain in enhancing disaster preparedness, including evacuation planning to minimize casualties. Physical characteristics and the preparedness of early warning systems are crucial in shaping community responses to landslides. This case study illustrates how a combination of steep slopes over 40 degrees, heavy rainfall intensity of more than 200 mm in one week, weak soil textures, and dense vegetation can trigger devastating landslides. However, landslides triggered by seismic activity result in significantly higher fatalities, and special attention is needed in areas prone to landslides and earthquakes, as happened in Nepal (highland and mountainous climate). In China (subtropic region), landslides are primarily triggered by moisture-saturated soils, which are vulnerable to ground motion, particularly during prolonged rainfall. In Indonesia as tropical region, landslides triggering evacuation predominantly occur in areas with highly erodible and unstable soils, exacerbated by high rainfall. Conclusion: Evacuation planning must be more adaptive and supported by GIS technology to identify high-risk areas. Globally, evacuation success relies on infrastructure, community awareness, and disaster preparedness. Novelty/Originality of thid article: This study highlights the importance of crisis management strategies tailored to the specific landslide characteristics of each region, as well as the crucial role of community involvement and technology in ensuring effective evacuations.